Cigarette Smoke Promotes Interleukin-8 Production in Alveolar Macrophages Through the Reactive Oxygen Species/Stromal Interaction Molecule 1/Ca2+ Axis - Zhu, Xianying; Zhan, Yuan; Gu, Yiya; Huang, Qian; Wang, Ting; Deng, Zhesong; Xie, Jungang (Frontiers in Physiology, 2021)
Chronic obstructive pulmonary disease (COPD), primarily attributed to cigarette smoke (CS), is characterized by multiple pathophysiological changes including oxidative stress and inflammation production. Stromal interaction molecule 1 (STIM1) is a Ca2+ sensor which regulates Ca2+ entry in multiple cells. The current study is aimed to explore the connection between oxidative stress and inflammation related to CS, as well as the function and mechanism of STIM1 thereinto. Here, we demonstrated the critical role of ROS/STIM1/Ca2+ axis in CS-induced IL-8 secretion of human alveolar macrophages. Specifically, increased reactive oxygen species (ROS) levels in lung tissues were observed in smokers with or without COPD than those in healthy non-smokers. Elevated STIM1 expression was observed in lung tissues of COPD patients and positively associated with ROS levels, while negatively related to pulmonary function. STIM1 expression was enhanced in human bronchoalveolar lavage fluid (BALF) macrophages of COPD patients and PMA-differentiated THP-1 macrophages stimulated by CSE. Additionally, CSE-induced STIM1 increase in PMA-differentiated THP-1 macrophage was inhibited by pretreatment with N-acetyl-L-cysteine (NAC), the ROS scavenger. Meanwhile, we determined that transfection with siRNA of STIM1 and pretreatment of NAC alleviated intracellular Ca2+ enhancement and IL-8 release induced by CSE. Furthermore, pretreatment with SKF-96365 and 2-APB, the pharmacological inhibitors for Ca2+ influx, ameliorated the CSE-induced IL-8 production. Summarily, our study demonstrate that CSE-induced ROS production may up-regulate STIM1 expression in macrophages, which further promotes the IL-8 release by regulating Ca2+ entry. Therefore, STIM1 may play a crucial role in cigarette smoke-induced ROS-inflammation response and participate in COPD pathogenesis.